Synthesis, Crystal Structure, DFT Calculations and Hirshfeld Surface Analysis of 3-Chloro - Ramalingam, Arulraj; Kansiz, Sevgi; Dege, Necmi; Sambandam, Sivakumar (Springer/Plenum Publishers, 2021)
The 3-chloro-2,6-bis(4-chlorophenyl)-3-methylpiperidin-4-one (CCMP) compound have been characterized by FT-IR,H-1-NMR,C-13-NMR,H-1-H-1 NOESY spectroscopy and single-crystal X-ray diffraction. The title compound crystallizes in the orthorhombic space groupPna21. The single crystal measurements reveal a distorted chair conformation [puckering parameter Q = 0.557 (3) A degrees; theta = 167.8 (3)degrees and psi = 206.8 (13)degrees]. The optimized geometric parameters and frequency values were theoretically calculated using DFT/B3LYP method with B3LYP/6-31+G(d,p) basis set. The XRD single crystal measurement parameters are good agreed with the optimized parameters. The spectral and optimized parameters showed that the piperidine-4-one ring adopts normal chair conformation with equatorial orientations of all the substituents except chlorine. The frontier molecular orbitals HOMO and LUMO were computed to know the chemical reactivity and kinetic stability of the molecular compound. Hirshfeld surface analysis was also performed. Hirshfeld surface analysis (d(norm)surface, two-dimensional fingerprint plots and molecular electrostatic potantials) revealed the nature of intermolecular interactions. The most important contributions for the crystal packing are from H center dot center dot center dot H (35%), Cl center dot center dot center dot H/H center dot center dot center dot Cl (32.3%), C center dot center dot center dot H/H center dot center dot center dot C (15%) and O center dot center dot center dot H/H center dot center dot center dot O (7.5%) interactions. Graphic In this study, spectroscopic properties of a new piperidine-4-one crystal compound and it's DFT structural investigation compared with experimental were gained to literature. [GRAPHICS] .
Sambandam, Sivakumar/0000-0001-8407-4768; Ramalingam, Arulraj/0000-0002-1412-0623
Keywords: Piperidin-4-One; DFT; HOMO-LUMO; MEP; Hirshfeld Surface Analysis; DFT/B3LYP/6-31+G(D,P)